1991
DOI: 10.1002/jbm.820251207
|View full text |Cite
|
Sign up to set email alerts
|

Lysine‐enhanced glutaraldehyde crosslinking of collagenous biomaterials

Abstract: Crosslinking of collagenous biomaterials currently employs the use of glutaraldehyde. The putative enhancement of glutaraldehyde crosslinking by lysine was investigated in three model systems: bovine pericardium, collagen membranes, and bovine serum albumin. Repetitive sequential treatment of bovine pericardium with glutaraldehyde and lysine and finally with formaldehyde produced a matrix which, by the two criteria used (shrinkage temperature and urea/SDS soluble collagen), was shown to be more highly crosslin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 20 publications
0
22
0
3
Order By: Relevance
“…Collagen scaffolds were treated with glutaraldehyde, a known protein cross-linker, 23 and PGG, a compound known to interact with proline-rich proteins such as collagen. 24 Samples were then tested in vitro for resistance to collagenase, mechanical properties, and thermal denaturation characteristics.…”
Section: Cross-linking Evaluationmentioning
confidence: 99%
“…Collagen scaffolds were treated with glutaraldehyde, a known protein cross-linker, 23 and PGG, a compound known to interact with proline-rich proteins such as collagen. 24 Samples were then tested in vitro for resistance to collagenase, mechanical properties, and thermal denaturation characteristics.…”
Section: Cross-linking Evaluationmentioning
confidence: 99%
“…The possible range of such alternative crosslinks is relatively broad, including the bridging of activated carboxyl groups with diamines 2,11 and the use of glutaraldehyde for crosslinking amino groups of the tissue with unreacted amines of equally introduced aliphatic diamines. 12 Since glutaraldehyde-treated tissue containing additional diamine bridges was shown to nearly eliminate graft-specific antibody induction, 2,11 we chose a similar but purely amino group-dependent crosslink augmentation 12 used in previous rat studies. 7,8 The aim of the present study was (1) to confirm in a sheep circulatory model that the mitigating effect of higher glutaraldehyde concentrations on tissue calcification can be significantly enhanced by the introduction of additional diamine bridges, and (2) to correlate crosslink density with bioprosthetic mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…As reported above, DSC studies showed there was a drastic decrease in the shrinkage temperature of oxazolidine tanned deaminated hide powder compared to oxazolidine tanned raw hide powder. Earlier reports hypothesized that this was due to cross-links being formed between the -NH 2 groups of lysine and the aldehydic reagents through the Mannich reaction resulting in inter fibril cross-links [3,30]. Amino acid analysis, however, did not show any difference in the amount of lysine or hydroxylysine both before and after tanning with oxazolidines, showing that there was no irreversible binding between these amino acids and oxazolidines.…”
Section: Amino Acid Analysismentioning
confidence: 77%